2007
DOI: 10.1590/s0034-89102007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Distorções causadas pelas ações judiciais à política de medicamentos no Brasil

Abstract: The majority of demands for drugs that have led to legal proceedings could be avoided if two SUS directives were followed, namely the organization of oncology services and the observance of reporting on essential medicines. Failure to do so causes a breakdown in the National Drug Policy, in equality of access and in the rational use of drugs within the National Health System.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
75
1
107

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(192 citation statements)
references
References 11 publications
9
75
1
107
Order By: Relevance
“…c Currently, there are fi ve classes of drugs: analgesics, nonsteroidal anti-infl ammatory drugs (NSAIDs), corticosteroids, disease-modifying Private lawyers prevailed in lawsuits fi led in Minas Gerais, a situation observed in different parts of the cuntry. 5,8,10,13 However, the Public Defender's Offi ce of Minas Gerais was responsible for most cases related to four of the 18 drugs most in demand, which is similar to the fi ndings by Messeder et al (2005) and Sant'ana (2011). 9,11,d A low frequency of legal proceedings fi led by free legal assistance centers linked to law faculties was observed.…”
Section: Discussionsupporting
confidence: 75%
“…c Currently, there are fi ve classes of drugs: analgesics, nonsteroidal anti-infl ammatory drugs (NSAIDs), corticosteroids, disease-modifying Private lawyers prevailed in lawsuits fi led in Minas Gerais, a situation observed in different parts of the cuntry. 5,8,10,13 However, the Public Defender's Offi ce of Minas Gerais was responsible for most cases related to four of the 18 drugs most in demand, which is similar to the fi ndings by Messeder et al (2005) and Sant'ana (2011). 9,11,d A low frequency of legal proceedings fi led by free legal assistance centers linked to law faculties was observed.…”
Section: Discussionsupporting
confidence: 75%
“…O predomínio da atuação da Defensoria Pública neste âmbito também foi observado por Messeder et al 16 , no Estado do Rio de Janeiro, e por Romero 17 , no Distrito Federal. Estudos realizados em outros estados -Vieira & Zucchi 18 , no Município de São Paulo; Marques & Dallari 19 , no Estado de São Paulo e Pereira et al 20 , no Estado de Santa Catarina -referiram ser a maior parte das ações conduzidas por advogados particulares. Há dois aspectos que devem ser aprofundados para entendermos este dado.…”
Section: Discussionunclassified
“…11,21 The estimated values of the annual treatments of the therapeutic classes most demanded judicially were burdensome. Comparison between these values and the gross domestic product (GDP) per capita of Brazil (almost R$ 17,500 in 2010) d and the average monthly income of Brazilian families (R$ 2,763.47), e corroborates the arguments of the legal decisions concerning the insuffi ciency of purchasing power among the population for buying these medications.…”
Section: Discussionmentioning
confidence: 99%
“…7 The number of lawsuits against local governments can reach close to seven thousand per year in Brazil, representing annual expenditures of up to R$ 60.4 million ($ 60.4 million). 3,4,11,21 Concession of medications is considered to be a means of judicialization of healthcare policy. 5 Researchers have suggested that judicial decisions do not take into account the possibility that there may be infl uences external to the political system capable of interfering in the incorporation of therapeutic innovations within the Brazilian National Health System (Sistema Único de Saúde, SUS), such as pressure from the pharmaceutical industry or from doctor and patient associations.…”
mentioning
confidence: 99%
See 1 more Smart Citation